(untitled) (Journal of Economic Research & Business Administration, 2016)
The main purpose a comprehensive overview of the various aspects of the development of transport and logistics system in Kazakhstan and perspectives of its further development in accordance with current international trends in the field of transport and logistics. Implementation of transport and transit potential of the Republic of Kazakhstan stands as a separate aspect of the task of forming a basis for a qualitative breakthrough in the economic development of the country. This aspect requires the provision to increase the attractiveness and create a modern and efficient transport and logistics system. Importance of work is that the logistics and transport are one of the priority directions of realization of strategy "Ka- zakhstan-2050". Considering geographical and strategic position of the country in questions of formation of the international corridors, it is possible to declare with confidence that transport in Kazakhstan - one of priority aspects of development.